Determinants of continuation on HIV pre-exposure propylaxis among female sex workers at a referral hospital in Uganda: a mixed methods study using COM-B model - Kawuma, Samuel; Katwesigye, Rodgers; Walusaga, Happy; Akatukunda, Praise; Nangendo, Joan; Kabugo, Charles; Kamya, Moses R; Semitala, Fred C (BioMed Central Ltd, 2025)
Female sex workers (FSWs) have the highest HIV prevalence in Uganda. Pre-exposure prophylaxis (PrEP) has been recommended as a key component of the HIV combination prevention strategy. Although patient initiation of PrEP has improved, continuation rates remain low. This study evaluated PrEP continuation among FSWs and explored potential determinants of PrEP adherence within a public referral hospital in urban Uganda. We conducted an explanatory sequential mixed method study at Kiruddu National referral hospital in Uganda. Secondary data on socio demographic characteristics and follow up outcomes of at least one year was collected for all FSWs who were initiated PrEP between May 2020 and April 2021 and data analyzed on July 15,2023. We used Kaplan-Meier survival analysis to evaluate continuation on PrEP from time of initiation and follow-up period. The capability, opportunity, and motivation to change behaviour model was used to explore perspectives and practices of FSWs (n = 24) and health care providers (n = 8) on continuation on PrEP among FSWs, using semi structured interviews. The qualitative data was deductively coded and analyzed thematically, categorizing the themes related to PrEP continuation as facilitators and barriers. Of the 292 FSWs initiated on PrEP, median age was 26 years (interquartile range, 21-29), 101 (34.6) % were active on PrEP, 137 (46.9%) were lost to follow-up, 45 (15.4%) were no longer eligible to continue PrEP, eight (2.7%) were transferred out and one (0.3%) had died. Median survival time on PrEP was 15 months (Interquartile range IQR, 3-21). The continuation rates on PrEP at six (6) and 12 months were 61.1% and 53.1%, respectively. Facilitators of PrEP continuation included awareness of risk associated with sex work, integration of PrEP with other HIV prevention services, presence of PrEP Peer support and use of Drop-in centers. The barriers included low community awareness about PrEP, high mobility of sex workers, substance abuse, and the unfavorable daytime clinic schedules. However, the quantitative findings from the multivariable Cox Proportional Hazards Model did not align with the reported findings for the qualitative evaluation. Continuation on PrEP remains low among FSWs. Interventions for PrEP continuation should address barriers such as low community awareness of PrEP, substance abuse and restrictive health facility policies for scale of the PrEP program among FSWs in Uganda. Integration of PrEP with other services and scale up of community PrEP delivery structures may improve its continuation.